2019
DOI: 10.1017/s0950268819000621
|View full text |Cite
|
Sign up to set email alerts
|

HPV infection in semen: results from a new molecular approach

Abstract: Human papillomavirus (HPV) is the agent of the most common sexually transmitted diseases causing a variety of clinical manifestations ranging from warts to cancer. Oncogenic HPV infection is the major cause of cervical cancer and less frequently of penile cancers. Its presence in semen is widely known, but the effects on fertility are still controversial. We developed a new approach to evaluate virus localisation in the different semen components. We analysed also the specific genotype localisation and viral D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
(47 reference statements)
2
23
0
1
Order By: Relevance
“…Concern over subfertility in HPV-positive men has received far less attention in previous qualitative studies. The data support the presence of HPV in semen and its proposed role in decreased fertility (20,21). Other studies indicated that HPV infection of semen represents a risk factor for male fertility abnormality (1,3).…”
Section: Discussionsupporting
confidence: 78%
“…Concern over subfertility in HPV-positive men has received far less attention in previous qualitative studies. The data support the presence of HPV in semen and its proposed role in decreased fertility (20,21). Other studies indicated that HPV infection of semen represents a risk factor for male fertility abnormality (1,3).…”
Section: Discussionsupporting
confidence: 78%
“…Сперма является одним из субстратов инфицирования ВПЧ, вирусы выявляются в семенной жидкости, в негерминативных клетках эякулята и в сперматозоидах [36]. Продемонстрировано наличие ДНК ВПЧ в очищенной фракции подвижных сперматозоидов [37].…”
Section: вирус папилломы человекаunclassified
“…Special high-risk clinical conditions may also be considered as a new potential target population: patients with inflammatory bowel disease (IBD), patients under biological treatment, transplanted subjects [ 76 ], and subfertile men/couples [ 77 , 78 , 79 , 80 , 81 ]. How the issue of HPV vaccination can be addressed in reproductive health to prevent subfertility and/or reproductive failure (embryo quality) in couples that seek pregnancy naturally or through in vitro fertilization is still unsettled.…”
Section: Special Populationsmentioning
confidence: 99%
“…Although meta-analysis suggests that HPV seminal infection can affect male fertility, the exact pathophysiological mechanism remains unclear [ 82 ]. A recent study described a new molecular approach to distinguish different HPV genotypes’ sperm infections and to observe the possible effects on semen [ 79 ]. Furthermore, the reported positive impact on the reproductive outcome of adjuvant HPV vaccination in infertile couples with HPV semen infection should be further investigated [ 83 , 84 , 85 ].…”
Section: Special Populationsmentioning
confidence: 99%